2017
DOI: 10.1103/physrevb.95.155117
|View full text |Cite
|
Sign up to set email alerts
|

(LaTiO3)n/(LaVO3)n as a model system for unconventional charge transfer and polar metallicity

Abstract: At interfaces between oxide materials, lattice and electronic reconstructions always play important roles in exotic phenomena. In this study, the density functional theory and maximally localized Wannier functions are employed to investigate the (LaTiO3)n/(LaVO3)n magnetic superlattices. The electron transfer from Ti 3+ to V 3+ is predicted, which violates the intuitive band alignment based on the electronic structures of LaTiO3 and LaVO3. Such unconventional charge transfer quenches the magnetism of LaTiO3 la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Considering that we find the 1/1 superlattice to be metallic, a more systematic study comparing the properties of bulk solid solutions with short-period superlattices of similar composition would be instructive. Note that DFT+U calculations for magnetically ordered LaVO 3 /LaTiO 3 superlattices also found the 1/1 case with layering perpendicular to [001] to be metallic, in agreement with our DFT+DMFT results, while other stacking directions turned out to be insulating [29]. Another study addressed the role of strain and polarity at interfaces of LaVO 3 and LaTiO 3 with various substrates [30], and suggested that the insulator-to-metal transition in both materials is due to a complex interplay of structural, and electronic degrees of freedom that affects the two materials in different ways.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Considering that we find the 1/1 superlattice to be metallic, a more systematic study comparing the properties of bulk solid solutions with short-period superlattices of similar composition would be instructive. Note that DFT+U calculations for magnetically ordered LaVO 3 /LaTiO 3 superlattices also found the 1/1 case with layering perpendicular to [001] to be metallic, in agreement with our DFT+DMFT results, while other stacking directions turned out to be insulating [29]. Another study addressed the role of strain and polarity at interfaces of LaVO 3 and LaTiO 3 with various substrates [30], and suggested that the insulator-to-metal transition in both materials is due to a complex interplay of structural, and electronic degrees of freedom that affects the two materials in different ways.…”
Section: Discussionsupporting
confidence: 88%
“…However, our calculations show that for all considered multilayers the charge transfer at the LaVO 3 /LaTiO 3 interface is in the opposite direction, i.e., charge is transferred from the Ti cations in LaTiO 3 to the V cations in LaVO 3 , thereby increasing the charge imbalance of the d states at the interface. This is also in qualitative agreement with recent DFT+U calculations for magnetically ordered LaVO 3 /LaTiO 3 superlattices [29]. Furthermore, the charge transfer is strongly localized at the interface, converging back to bulk-like occupations within only three layers.…”
Section: B Charge Transfersupporting
confidence: 91%
“…In particular, straining interfaces in oxide heterostructures provides a fertile ground for emergent properties such as ferroelectricity [10,11], high-temperature superconductivity [12],piezoelectricity [13], magnetoresistance [14], structural reconstructions [15], multiferroicity [16] and charge transfer [17,18]. Charge transfer is one important consequence of electronic reconstructions in oxide interfaces [19][20][21][22]. Indeed, in these systems the structural and electronic continuity define a set of band alignment rules, which yield electronic transfer from the high to the low energy bands.…”
Section: Introductionmentioning
confidence: 99%
“…A Similar type of asymmetric distortion has been shown to lead ferroelecricity with a net measurable in plane polarization for (YTiO 3 ) 2 /(YFeO 3 ) 2 and (LaTiO 3 ) 2 /(LaVO 4 ) 2 magnetic superlattices. Charge transfer across the interface is reported to be the origin of such ferroelectric mode [11,15]. Moreover, the FEL mode in a 2/2 SL demonstrates strong carrier concentration dependence, which is also a key characteristic of a polar metal [5].…”
mentioning
confidence: 96%
“…However, in 1965, Anderson and Blount first suggested that polar displacements, which drive a material from a highsymmetry paraelectric phase to a low-symmetry ferroelectric phase, could exist in a metal [3]. Recently, the observation of a ferroelectric-like structural transition in the metallic oxide LiOsO 3 [4] generated an interest in polar metals [5][6][7][8][9][10][11]. Fundamentally, there is no incompatibility between metallicity and polar or ferroelectric-like displacements [5].…”
mentioning
confidence: 99%